Exploring Students’ Reading Fluency and Accuracy through the Implementation of ORVT - Siahaan, Rismauli Diana Pudyastuti; Simanjuntak, Debora Chaterin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Reading is an indispensable foundational skill crucial for success in life. However, numerous Indonesian students encounter difficulties with reading comprehension, as highlighted in the PISA National Report. Addressing this challenge necessitates a focus on enhancing both reading fluency and accuracy. The Oral Reading Verification Test (ORVT) is a valuable tool to assess reading ability and guide interventions. This study used quantitative methods, focusing on improving students’ reading comprehension through the ORVT. A total of 61 junior high school students from grades VI, VII, and IX participated in the study, with assessment results revealing progress in comprehension and specific error patterns. Pronunciation errors topped the list in grades 7, 8, and 9, with an average percentage of 51.71%. The three classes’ achievement on the reading comprehension assessment reached an average of 85.1%, understanding well (complete). The results showed improvement in reading comprehension, highlighting areas of strength and improvement across different aspects of oral reading skills (highly satisfactory). This study underscores the effectiveness of ORVT in improving reading skills and emphasizes the importance of targeted support for reading comprehension.